2018
DOI: 10.1038/s41386-018-0201-y
|View full text |Cite
|
Sign up to set email alerts
|

NMDA-receptor independent actions of ketamine: a new chapter in a story that’s not so old

Abstract: adequately drive "downstream" nodes, a second stimulating site could enhance the network disruption. Fusing the anatomic and physiologic approaches into a dynamic, network-targeted approach to closed-loop DBS may be the next horizon for personalized treatment in severe psychiatric disorders. ACKNOWLEDGEMENTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…NMDA receptor antagonists did not show the rapid, effective, and long-lasting antidepressant effect that resembles ketamine [55]. Thus, ketamine effects that are independent of NMDA receptors have become a focus of research [56]. Here, we found that ketamine increased the activity of GSK-3β.…”
Section: Discussionmentioning
confidence: 69%
“…NMDA receptor antagonists did not show the rapid, effective, and long-lasting antidepressant effect that resembles ketamine [55]. Thus, ketamine effects that are independent of NMDA receptors have become a focus of research [56]. Here, we found that ketamine increased the activity of GSK-3β.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, in the hypothalamus, PC ae C36:5 decreased following either ketamine or (2 R ,6 R )-HNK treatment, and PC aa C36:6 also decreased following (2 R ,6 R )-HNK treatment. A reduction in the relative abundance of several PC species in the prefrontal cortex of rats was found after administration of the antidepressants maprotiline and paroxetine [ 82 , 88 ]. Paroxetine also increased levels of cholesterol and TGs, whereas fluoxetine decreased cholesterol and TG levels [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the effects of ketamine on the brain might be dose-dependent and its actual effect is less obvious. Apart the well-described inhibition of the NMDA receptors ( Autry et al, 2011 ), ketamine seems to have a plethora of different target sites, from sodium channels to cholinergic, dopamine, and opioid receptors ( Wray and Rasenick, 2019 ) ( Sleigh et al, 2014 ): this makes characterization of the molecular and cellular pathways involved challenging.…”
Section: Limitationsmentioning
confidence: 99%